Indonesian Students' Perspectives on Problem-Based and Multicultural Learning in Basic Reading Comprehension - Utami, Elva; Arono, Arono; Yunita , Wisma; Safnil, Safnil; Kencana, Nila; Hermansyah, Sam (EduBase : Journal of Basic Education, 2025)
Objective: This study examines students' views on the use of Basic Reading Comprehension materials developed with the Problem-Based Learning (PBL) model and a multicultural-based approach. Novelty: The novelty of this study lies in the integration of PBL with a multicultural approach to improve students' reading comprehension, motivation, and learning engagement in a diverse educational environment. Methods: This study used a qualitative approach involving 300 Indonesian students. Data were collected through semi-structured interviews and open-ended questionnaires, then analyzed thematically to produce the effectiveness of this approach. Results: Students felt more motivated and active in discussions when the material combined problem-solving tasks and culturally relevant content. PBL improved the ability to understand texts through critical thinking and collaboration, while the multicultural approach helped students integrate the material with their cultural background, thus encouraging inclusivity and awareness of diversity. Challenges found include the need for more assistance for students who are not familiar with PBL. Conclusion: The integration of PBL with multicultural-based materials can significantly improve reading learning by making it more interactive, inclusive, and meaningful. It is recommended to provide additional support for diverse learners and develop more culturally responsive teaching materials.